Special papersNew oral anticoagulants – will they be used with antiplatelet drugs in patients with atrial fibrillation after acute coronary syndrome? - Gorczyca-Michta, Iwona; Wożakowska-Kapłon, Beata (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Atrial fibrillation (AF) is the most frequent indication for oral anticoagulation. Dual antiplatelet treatment with aspirin and clopidogrel is an antithrombotic treatment recommended after acute coronary syndrome and/or coronary artery stenting. The evidence for optimal antiplatelet therapy for patients who underwent a long-term treatment based on oral anticoagulation is strong. A direct thrombin inhibitor, dabigatran, as well as direct factor X inhibitors, apixaban and rivaroxaban, are now being commonly used in the prevention of thromboembolic complications of AF. Given the consistent increase in bleeding and the less consistent reduction in ischaemic events, the overall profile of adding new oral anticoagulants to antiplatelet treatment after acute coronary syndrome is unknown.